Peran Rasuna Said Dalam Parlemen Indonesia Tahun 1945-1965 - Anisa Rahmawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jember, 2025)
Rasuna Said was a prominent female figure from West Sumatra who played an active role in Indonesian independence and served as a member of parliament after independence. Rasuna Said's role in the Indonesian Parliament from 1945–1965 focused on her advocacy for the political, social, and economic rights of the people and women in the post-independence legislative body. The background of this research stems from the limited in-depth study of women's contributions to parliament in the early days of the Republic of Indonesia. The purpose of this study is to analyze Rasuna Said's life journey before entering parliament, trace her political activities as a member Working Committee of the Central Indonesian National Committee, the Provisional People's Representative Council, and the Supreme Advisory Council, and examine the impact of her struggle on the social structure of Indonesian society. This study uses a historical research method with four stages: heuristics, criticism, interpretation, and historiography. The approach used is political sociology with Levinson's role theory to explain the dynamics of Rasuna Said's socio-political behavior in the context of public office. The results show that Rasuna Said played an active role in shaping the direction of national policy, particularly through interpellation and criticism of economic, social, and foreign policy. She also contributed to the development of policies that favored the common people and women. The conclusion of this study confirms that Rasuna Said's role in parliament was not only to champion gender equality, but also to strengthen the foundations of democracy and women's participation in national politics.
Validasi 26 Mei_Reva
Keywords: parliament; politics; women